Mesoporous Silica MCM-41 Supported N-Heterocyclic Carbene-Pd Complex for Heck and Sonogashira Coupling Reactions - Sarkar, Shaheen M.; M. M., Yusoff; Lutfor, M. R. (John Wiley & Sons, Inc., 2015)
Heterocyclic carbene-Pd complex was anchored onto themesoporous silicaMCM-41 which exhibits high catalytic activity in Heck reaction under phosphine free reaction conditions for the reaction of iodo/bromoarenes with olefinic compounds such as butyl acrylate, isopropyl acrylate and styrene. This catalytic system also showed high activity for Sonogashira coupling reaction of various aryl halides under copper, phosphine and solvent-free reaction conditions. The air and thermally stable catalyst were reused several times without significant loss of its activity. High efficiency of the catalyst along with its recycling ability and the rather low Pd-loading demonstrated in both Heck and Sonogashira coupling reactions are the merits of the presented catalyst system.